In search of transparent networks. - Morris, A.S., III (IEEE spectrum)
Optical transmission networks work well, but their switchgear is opaque in that it must convert signals to electronic form before routing them. In this paper, the author presents a look at how the candidate technologies for all-optical, or transparent, switching work and stack up against each other